Scalable ultrathin solid electrolyte from recycled Antheraea pernyi silk with regulated ion transport for solid-state Li–S batteries - Lu Nie; Yang Li; Xiaoyan Wu; Mengtian Zhang; Xinru Wu; Xiao Xiao; Runhua Gao; Zhihong Piao; Xian Wu; Ya Song; Shaojie Chen; Yanfei Zhu; et al. (eScience)
Ultrathin solid-state electrolytes (SSEs) with rapid Li+ transport are ideal for developing high-energy-density all-solid-state lithium metal batteries. However, a significant challenge remains in balancing the intrinsic trade-off between electrochemical performance and mechanical properties. Herein, Antheraea pernyi fibers recycled from waste silk textiles are utilized as the raw materials to construct a porous and strong supporting skeleton for fabricating ultrathin SSE. This skeleton not only provides efficient three-dimensional Li+ transport channels, but also immobilizes Li-salt anions, resulting in homogenized Li+ flux and local current density distribution, thereby promoting uniform Li deposition. As a result, the obtained ultrathin SSE exhibits excellent ion-regulated properties, enhanced electrochemical stability, and superior dendrite suppression. Additionally, the formation of an inorganic-rich solid electrolyte interface layer is beneficial for stabilizing the interface contact between the SSE and Li anode. The solid-state Li|sulfurized polyacrylonitrile (Li|SPAN) cell delivers an excellent capacity retention of 92.3% after 500 cycles at 1 ​C. Moreover, the prepared high-voltage Li|LiCoO2 pouch cell exhibits a capacity retention of 90.1% at 0.2 ​C after 200 cycles. This work presents an economically effective strategy for reutilizing waste textiles as ion-conducting mechanical supports for energy storage applications.